THE IMPACT OF PARENTING EDUCATION OF KNOWLEDGE, PRACTICE OF THE FIRST 1000 DAYS OF LIFE AND PARENTING STYLE AMONG MOTHERS IN MAKASSAR: PRE-POST STUDY - Trisnawaty Trisnawaty; Yusma Indah Jayadi; Tarmizi Thalib; Nikmah Utami Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Various parenting problems arise from the inability of parents to provide care and education in their homes. Psychological conditions of parents cause various psychological problems in children, in addition to the awareness of parents about the importance of 1000 Days of Life can result in the next generation not only in physical problems but also mental and intelligence. Online education classes are a means for parents to get structured information. The purpose of this study was to analyze whether parenting education classes are really effective in increasing parents' knowledge and actions about the First 1000 Days of Life and appropriate parenting patterns. This research is an experimental study with a one shot case study experimental design, with a sample of 115 mothers who have attended parenting education classes aged 20-45 years. Parenting education is the independent variable while parenting patterns, knowledge and actions of parents about the First 1000 Days of Life are as the dependent variable. The research instrument uses a parenting style scale, a knowledge questionnaire and a 1000 Days action scale that has been tested for validity and reliability. Data analysis used Paired Sample T-Test for describing the parenting patterns and Wilcoxon Test for parents' knowledge and actions about the First 1000 Days of Life. The results showed that classroom education had a significant effect on parenting (p=0.000), as well as the knowledge and actions of 1000 Days of parents (p=0.000). This shows that the education class is effective in educating parents about parenting and 1000 Rights. The Parenting education has a significant effect on parenting patterns, knowledges and actions about the First 1000 Days of Life.